Examining the impact of job crafting, work-life balance, and procrastination on performance enhancement - Dorothea Wahyu Ariani (Problems and Perspectives in Management)
This study aims to investigate the impact of job crafting on work-life balance and employee achievement, specifically in-role performance and work-related procrastination, as positive and negative outcomes, respectively. A survey questionnaire was administered to 1,032 employees from micro, small, and medium enterprises in Indonesia. Factor analysis and internal consistency testing were used to assess the measuring instruments. The relationship model was tested using structural equation modeling with a two-step approach. The paper found a relationship among the three dimensions of job crafting and their correlation with work-life balance, procrastination, and in-role performance. Work-life balance and in-role performance exhibited a significant negative relationship with procrastination. These results show that the approach aspect of job crafting can enhance both work-life balance and in-role performance. The model fit to the data is very good (CFI (0.996 > 0.95), NFI (0.985 > 0.90), SRMR (0.004 < 0.08), GFI (0.996 > 0.95), TLI (0.954 > 0.90), AGFI (0.919 > 0.90) with a small normed chi-square (χ2/df = 11.973). The influence of job crafting dimensions on procrastination varied. The findings further strengthen the notion that the proactive element of job crafting positively influences behavior through offering feedback, setting high targets for employees, and expanding the scope of work to enhance their complexity. However, the avoidance aspect of job crafting remains inconsistent and requires further research. The practice of job crafting should be encouraged in the workplace. AcknowledgmentHeartfelt gratitude is extended to the employees of MSMEs actively engaged in this research.